Theoretical and experimental study on shearing capacity of concrete beams reinforced with carbon fiber truss. (15th February 2021) - Guo, Songsong; He, Haifang; Liu, Chao; Cheng, Shoushan; Liu, Hongyi
Abstract: In recent years, small and medium-span reinforced concrete (RC) beams have suffered severe cracking at bearings and quarter span, and shear diseases have been a severe phenomenon for bridges. Currently, many methods are used for shear strengthening of RC beams, but some questions such as low reinforcement efficiency and poor durability still exist. Although externally bonded fiber reinforced polymer (FRP) has been widely used to strengthen concrete bridges, the utilization efficiency of FRP still needs to be improved. A closed FRP truss combining externally U-type and side bonded FRP is proposed, which aims to enhance the utilization efficiency of FRP and the shear capacity of RC beams in this paper. The calculation model is established to predict the shear capacity of RC beams strengthened with FRP truss by theoretical study, model tests and numerical simulations. FRP truss obviously enhances the shear capacity of RC beams and the utilization efficiency of FRP. Finite element method is used to analyze the influence of the stirrup ratio on the strengthening efficiency of FRP truss, which proves that reinforcement effects gradually increase with the decrease of stirrup ratio. Under ideal condition, FRP truss presents tensile failure when stirrup ratio is less than 0.18%.